ICER, ISPOR AND QALYs: A Tale of Imaginary Worlds - Paul Langley (University of Minnesota Libraries Publishing, 2019)
Previous commentaries in the Formulary Evaluation section of INNOVATIONS in Pharmacy have pointed to the lack of credibility in modeled claims for cost-effectiveness and associated recommendations for pricing by the Institute for Clinical and Economic Review (ICER). The principal objection to ICER reports has been that their modeled claims fail the standards of normal science: they are best seen as pseudoscience. The purpose of this latest commentary is twofold: first, to review the latest report by the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) on standards and value claims for modeling imaginary cost-per-quality life year (QALY) worlds in health technology assessments and (ii) given ICER's commitment to ISPOR standards, to consider the credibility of ICER's QALYs. The concern is that ICER gives the impression that there is a common and agreed utility metric to support QALY constructs and that there is an agreed standard for creating QALYs within the imaginary reference case meme. The purpose of this commentary is to emphasize that there is no 'gold standard' QALY, let alone a 'gold standard' utility metric. A QALY is what you assume the QALY should be; it is an artificial construct which allows any number of competing QALYs to be generated for the same target population under different imaginary constructs. Similar objections apply to the application of willingness-to-pay thresholds to support ICER's business case as the sole arbiter, in pole position, of health technology assessments to support pricing recommendations. In the US.  A threshold has to be defined for the QALYs and costs captured, by assumption, within the model. Even for the same target patient population a $50,000 cost per QALY threshold will yield different pricing recommendations depending upon the assumptions driving the QALY estimate, such as choice of utility metric, time spent by stage of disease, frequency and severity of adverse events and costs. While this is an obvious point, it appears not to occur to those who, with a limited technical understanding of how the ICER model is constructed (and ICER is not given to extended technical explanations) take at face value the ICER imaginary construct and the QALY value judgements. Of course, it is also beside the point that the ICER reference case imaginary world was never intended to support empirical assessments of the claims made; we have no idea of whether it is right, if it is wrong and, over the lifetime perspective, we will never know and were never intended to know.   Article Type: Commentary